Effect of Qizhitongluo capsule on lower limb rehabilitation after stroke: A randomized clinical trial. (March 2021) - Yu, Yanan; Tang, Lu; Cui, Fangyuan; Jiao, Fuying; Zhang, Dong; Ma, Jin; Ding, Wentao; Yu, Yingmei; Zhang, Bo; Meng, Zhihong; Dai, Xiaoyu; Liu, Dequan; et al.
Graphical abstract: Abstract: Background: An individual's level of lower limb motor function is associated with his or her disability level after stroke, and motor improvement may lead to a better prognosis and quality of life. Data from animal models show that Qizhitongluo (QZTL) capsule facilitates recovery after focal brain injury. We aimed to validate the efficacy and safety of the QZTL capsule for promoting lower limb motor recovery in poststroke patients. Methods: In this randomized, multicenter, double-blind, placebo- and active-controlled trial from 13 sites in China, participants with ischemic stroke and Fugl-Meyer motor scale (FMMS) scores of <95 were eligible for inclusion. Patients were randomly assigned in a 2:1:1 ratio to the QZTL group, Naoxintong (NXT) group or placebo group for 12 weeks at 15–28 days after the onset of stroke. The primary outcome was the change in the Lower Limb FMMS (FMMS-LL) score from baseline over the 12-week intervention period. Results: 622 participants were randomly assigned to the QZTL group (309), NXT group (159), or placebo group (154). The FMMS-LL score increased by 4.81 points (95 % CI, 4.27–5.35) in the QZTL group, by 3.77 points (95 % CI, 3.03–4.51) in the NXT group and by 3.00 points (95 % CI, 3.03–4.51) in the placebo group at week 12. The QZTL group showed significantly larger improvements compared with the placebo group at each interview from weeks 4–12 (difference, 0.89 [0.30, 1.49] at week 4, P = 0.0032; difference, 1.83[1.01, 2.66] at 90 days poststroke, P < 0.0001; difference, 1.81[0.88, 2.74] at week 12, P = 0.0001). Conclusion: The QZTL capsule is an effective treatment for lower limb motor impairment. The finding indicates that the QZTL capsule may be used as a potential new strategy for stroke rehabilitation.